Identification Key to the Indigeneous Indonesian Genera of Myrtaceae - Lyn A. Craven; Siti Sunarti; Deden Mudiana; Titut Yulistyarini; Marfu'ah Wardani (PTTI, 2002)
Kunci identifikasi marga Myrtaceae asli Indonesia